The impact of subjective social class and social mentality on public attitude in the Third Distribution - Li, Minrui; Zhou, Runan; Chen, Yuhou; Zhong, Yilin (Frontiers in Political Science, 2022)
The public's social mentality has an essential influence on the attitude toward participating in the Third Distribution and the implementation of the policy. From the perspective of subjective social class and prosocial behavior, based on social cognition theory and existing literature, we established the citizen class-society mentality and attitude model in China. The model mechanism is verified by a questionnaire survey of citizens' subjective social class, sense of social fairness, and subjective well-being. The results showed that subjective social class positively influenced individuals' attitudes toward participation in the Third Distribution, but expected social class negatively moderated the relationship between citizens' participation experiences and attitudes. In addition, the subjective social class in the past influenced individuals' attitudes to participation in the third distribution through subjective well-being and the sense of social fairness, and the effect of the intermediary path of subjective well-being was stronger than the sense of social justice.